Double-decker sensor phthalocyanines functionalized with 1-hydroxyhexane-3-ylthio moieties; synthesis, characterization, electrical properties and H- or J- type aggregation studies - Bilgicli, Ahmet T.; Gunsel, Armagan; Kandaz, Mehmet; Altindal, Ahmet; Comert, Huseyin (ELSEVIER SCIENCE SA, 2015)
In this study, we report the synthesis, characterization, aggregation and electrical properties of softmetal ionophore functional double-decker sensor-phthalocyanines, {([4,5,4',5'4 '',5 '',4 '',5']-octakis-(1hydroxyhexane-3-ylthio) phthalocyaninato lanthanium (HI)}) [M(Pc)21, fM = Lu3 (2), Yb3 (3) and La3+ (4)}. The new compounds have been characterized by elemental analysis, MS-TOF, UV-Vis, FT-IR, 1H NMR, and ESR spectral data. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) as complementary techniques were used for investigate the morphology of the 2, 3 and 4 complex. Functionalized phthalocyanines with 1-hydroxyhexane-3-ylthio moieties have been lead to selective metal ion sensor, such as Ag+ and Pd2+1. The temperature dependence of the dc and ac conduction properties of 2, 3 and 4 thin films have been investigated in the frequency range of 40 Hz-10(5) Hz and temperature range between 297 and 500 K. For complex 2 it was found that thermally activated band conduction is the dominant conduction mechanism at high temperatures whereas in the low temperature region the dependence of the dc conductivity on temperature followed Mott's variable range hopping (VRH) model. The ac conductivity showed strong dependence on both temperature and frequency. The temperature dependence of frequency exponent suggested a dominant hopping conduction process. (C) 2015 Elsevier BY. All rights reserved.
Keywords: Double-decker phthalocyanines; Silver and palladium ions; H- and J-aggregation; Sensor; Impedance spectroscopy; Conductivity; GAS-SENSING PROPERTIES; RARE-EARTH COMPLEXES; LUTETIUM(III) PHTHALOCYANINE; PHOTODYNAMIC THERAPY; THIN-FILMS; PART 4; ELECTROCHEMISTRY; NAPHTHALOCYANINE; SPECTROSCOPY; Chemistry